Decreased leukocyte exhaustion is associated with decreased IFN-β and increased α-defensin-1 levels in type-2 diabetes. (August 2022) - Shruthi, Sugumar; Sibi, Joy Manohar; Mohan, Viswanathan; Babu, Subash; Nirmaladevi, Veerakesan; Aravindhan, Vivekanandhan
Highlights: Reduced pan-leukocyte exhaustion was seen in type-2 diabetes. This was due to reduced circulating levels of IFN-β and increased levels of α-DEF-1. This was due to reduced secretion of IFN-β and increased secretion of α-DEF-1. The PU.1-IRF transcriptional network was largely unaffected. Redox stress along with reduced leukocyte exhaustion can fuel metainflammation. Abstract: Pan-leukocyte exhaustion is a physiological process associated with immune homeostasis. Too much of immune exhaustion can lead to immune impairment and increased susceptibility to infections and cancer; too little can lead to chronic inflammation. Since type-2 diabetes subjects have both impaired immunity and metainflammation, we looked at TLR induced pan-immune exhaustion and its regulation, in these subjects. TLR induced expression of PD-1 and CTLA-4 in T cells, B cells, monocytes and neutrophils, in whole blood cultures, were quantified by flowcytometry. Circulating levels and in vitro secretion of IFN-β and α-Defensin-1 (α-DEF-1) were quantified by ELISA. TLR induced expression of PU.1, IRF-3, -4 and -5 in whole blood cultures was quantified by qRT-PCR. Systemic lipid and protein peroxidation was quantified by spectrophotometry. TLR induced expression of PD-1 (in monocytes) and CTLA-4 expression (in B cells and neutrophils) were decreased in drug naive newly diagnosed diabetes patients. This was associated with decreased secretion and circulating levels of IFN-β and increased secretion and circulating levels of α-DEF-1 in these subjects. No major derangement in the transcriptional network was seen. Many of these defects were only partially rectified in those under treatment. Together, we hypothesize that the high defensin levels could inhibit TLR signalling leading to reduced IFN-β levels, which in turn could lead to reduced expression of PD-1 and CTLA-4 in the immune cells. This effect along with systemic redox stress could fuel metainflammation in type-2 diabetes.